In vitro fracture strength and patterns in root‐filled teeth restored with different base materials. (24th November 2017) - Chan, T; Küçükkaya Eren, S; Wong, R; Parashos, P
Abstract: Background: There is little research on the effects of an intermediate base on the fracture strength of root‐filled teeth. This study compared the fracture strengths and patterns of root‐filled teeth restored with intermediate bases of glass‐ionomer cement (GIC), zinc polycarboxylate cement (ZPC), dual‐cured resin composite (DCRC) and Biodentine ® under resin composite. Methods: Standardized cavities were prepared in 100 extracted human maxillary and mandibular premolars, and root canal treatment was performed. The teeth were stratified and randomly allocated to five groups ( n = 20): (i) GIC; (ii) ZPC; (iii) DCRC; (iv) Biodentine; and (v) prepared but unrestored (control). The teeth were subjected to an oblique, ramped load until fracture. The fracture loads, level, mode and location were recorded. Results: Mean fracture strengths of all restored groups were not significantly different amongst the groups. There were significant overall effects on mean fracture strength for tooth type ( P = 0.002) and buccolingual width of the crown ( P = 0.001). Conclusions: The four materials were appropriate intermediate bases. The laminate restorative technique promoted fracture strengths that are likely to withstand normal and maximum masticatory function. The base material can influence failure mode, which may have implications for the clinical presentation of fractures of root‐filled teeth.